ОБЛІКОВА ПОЛІТИКА ЩОДО ОСНОВНИХ ЗАСОБІВ - Кафка, С. М. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2018)
The article outlines the main points that it is advisable to take into account in the process of formation of the accounting policy regarding fixed assets, the proposals for the expediency of introducing changes to existing regulatory requirements in the assessment and calculation of depreciation of fixed assets in pledge and those temporarily withdrawn from operation in connection with their improved or preserved.